Unterwegs mit Andrzej Stasiuk. Fokus: Mitteleuropa - Joanna Firaza (Zagadnienia Rodzajów Literackich)
Travelling is the passion of the Polish, contemporary writer Andrzej Stasiuk. It is for him a goal in itself but also a point of reference for the definition of his own nation and country facing geopolitical change (My Europe, 2000; Dojczland, 2007; Waiting for the Turk, 2009), which constantly demands to be revised. Travelling serves the writer as a solitary but in the end illusory way of experiencing and capturing the material world in the face of perpetual annihilation. Stasiuk’s nostalgic journeys become a pretext for archiving the transient material world — Europe, which fades in front of our eyes and, by means of the author’s craft, metamorphoses into a myth, and makes the text another testimony of his geopoetics.